2013
DOI: 10.1016/j.bpj.2012.11.3835
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Flexural Rigidity of Rod Photoreceptors

Abstract: In vertebrate eyes, the rod photoreceptor has a modified cilium with an extended cylindrical structure specialized for phototransduction called the outer segment (OS). The OS has numerous stacked membrane disks and can bend or break when subjected to mechanical forces. The OS exhibits axial structural variation, with extended bands composed of a few hundred membrane disks whose thickness is diurnally modulated. Using high-resolution confocal microscopy, we have observed OS flexing and disruption in live transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Hendrickson, from a histological study of the retinas of adults and newborn babies, predicted that the human foveal cone density increased until around 5–8 years of age 19. An earlier study showed that a reduced number of discs reduced the magnitude of the outflow signal from the photoreceptors proportionately 20. The discs in the OSs of the photoreceptors are constantly being renewed.…”
Section: Discussionmentioning
confidence: 98%
“…Hendrickson, from a histological study of the retinas of adults and newborn babies, predicted that the human foveal cone density increased until around 5–8 years of age 19. An earlier study showed that a reduced number of discs reduced the magnitude of the outflow signal from the photoreceptors proportionately 20. The discs in the OSs of the photoreceptors are constantly being renewed.…”
Section: Discussionmentioning
confidence: 98%
“…They may be useful in the development of quantum computers as well. In addition, in accompany with some other researches on cone (Skaper, 2012) and rod (Haeri et al, 2013) cells may shed light and support progresses on the retina degeneration diseases. However, each proposed experiment should also describe plausible biophysical mechanisms that would explain how the quantum effects examined could affect neural signaling, which is left for future communications.…”
Section: Final Remarksmentioning
confidence: 68%
“…A random phase in the sinusoidal function was selected to represent Rho-mCherry expression unsynchronized among rods in the same retina [5,52]. Since induction may occur at any point in the varying G3 expression cycle, we expect a variety of Rho-mCherry induction response shapes (Figure 8C).…”
Section: Discussionmentioning
confidence: 99%